Manajemen Kurikulum Pendidikan Islam berbasis Life Skills di Sekolah Luar Biasa (SLB) Aneuk Nanggroe Kota Lhokseumawe - Kemala Hayani; Susi Yusrianti; Saifuddin Dhuhri (Journal of Islamic Education Leadership, 2023)
Islamic Education Curriculum Management based on Life Skills at the Aneuk Nanggroe Special School (SLB) in Lhokseumawe City. This study aims to describe life skills-based Islamic education curriculum management, starting from planning, organizing, implementing, and evaluating. The research approach is descriptive qualitative. The research location, Aneuk Nanggroe Special School (SLB), Lhokseumawe City. Data collection was carried out using field observation techniques, interviews, and documentation. Model data analysis techniques developed by Miles et al, namely data collection, data reduction, data presentation and drawing conclusions. The results showed that: Life Skills-based Islamic education curriculum planning at the Aneuk Nanggroe Special School (SLB) in Lhokseumawe City by formulating the vision, mission and goals of the school. Through the results of the Identification Assessment for Children with Special Needs (ABK), Islamic education programs are adjusted to the abilities of ABK children in each disability, preparing lesson plans and individual mentoring programs. (2). Organizing is done by compiling an organizational structure, forming an Assessment Team, allocating time for religious learning (3). The implementation of the Islamic education curriculum at Aneuk Nanggroe State SLB is carried out through morning habituation activities, religious programs every Friday, life skills education is carried out according to the abilities of ABK students who have been programmed in special programs (4) Evaluation of the Implementation of Life Skills-based Islamic education curriculum management for children with special needs is carried out on a macro and micro basis by stakeholders, school principals and the school supervision team